POST: Notes on Modern and Contemporary Art around the globe - The Museum of Modern Art (2013)
[Engl.:]The site is designed to encourage active participation; users and institutional partners are encouraged to upload their own findings and share their questions, together gaining broader exposure and expertise. Committed to investigating artistic practices that have historically been overlooked in MoMA’s collection and exhibitions, POST explores sites of experimental practices with an initial focus on regions that are the focus of C-MAP research: East Asia, Central and Eastern Europe, and Latin America and the Caribbean. Upon its launch, POST recently presented its first case study, in partnership with Keio University Art Center, featuring the archival materials of Sogetsu Art Center, an epicenter of avant-garde artistic experiments in Tokyo in the 1960s that hosted an exciting, rapid-fire series of programs in experimental music, jazz, and cinema. The initial presentation features essays, interviews, and works by artists related to Sogetsu Art Center—Shiomi Mieko, Yokoo Tadanori, Matsumoto Toshio, and Yamaguchi Katsuhiro—and artists who have been the subject of C-MAP research—Geta Brătescu, ChimPom, and Jikken Kobo, among others. The site is constantly evolving and will soon have case studies and themes focused on art in Eastern Europe and Latin America.